2017
DOI: 10.1111/cdev.12769
|View full text |Cite
|
Sign up to set email alerts
|

Children's Judgments and Reasoning About Same‐Sex Romantic Relationships

Abstract: Children's (5-, 7- to 8-, and 10- to 11-year-olds), and adolescents' (13- to 14-year-olds) judgments and reasoning about same-sex romantic relationships were examined (N = 128). Participants' beliefs about the acceptability and legal regulation of these relationships were assessed, along with their judgments and beliefs about excluding someone because of his or her sexual orientation and the origins of same-sex attraction. Older participants evaluated same-sex romantic relationships more positively and used mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In these domains, inferences of blame promote prejudice, and this is why inferences of biological determinism mitigate prejudice. By the same logic, inferences of structural determinism also often mitigate prejudice toward these identities ; though see Spence et al, 2018 for evidence that upbringing-related explanations for homosexuality do not effectively mitigate anti-gay attitudes).…”
Section: Social Status Disparities Identitiesmentioning
confidence: 98%
See 2 more Smart Citations
“…In these domains, inferences of blame promote prejudice, and this is why inferences of biological determinism mitigate prejudice. By the same logic, inferences of structural determinism also often mitigate prejudice toward these identities ; though see Spence et al, 2018 for evidence that upbringing-related explanations for homosexuality do not effectively mitigate anti-gay attitudes).…”
Section: Social Status Disparities Identitiesmentioning
confidence: 98%
“…Emerging research also suggests that children's essentialist views of homosexuality predict reduced prejudice toward LGBTQ people. Spence, Helwig and Cosentino (2018) assessed seven-to fourteen-year-old children's essentialist conceptions of same-sex attraction by asking them about the likelihood of various explanations for same-sex attraction and about whether a person could change their mind and decide to prefer other-sex partners. They also assessed children's anti-gay judgments, such as their views of whether same-sex relationships are "okay" and whether it is acceptable to socially exclude gays and lesbians.…”
Section: Prejudice-mitigating Consequences Of Social Essentialismmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern of results is in contrast to previous research of essentialism of categories like race and gender wherein higher essentialism is related to bias against low-status groups (e.g., Rhodes & Mandalaywala, 2017). However, recent work has found that essentialism can actually reduce children’s prejudice around body weight (Carvalho et al, 2021), sexual orientation (Spence et al, 2018), and incarceration status (Dunlea & Heiphetz, 2020). These studies suggests that particularly for stigmatized groups, essentialized thinking may lead to discounting agentic explanations of group differences, making an individual appear less “blame-worthy” (because they were “born that way”) for their stigmatized status (e.g., Peretz-Lange, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly problematic here since some adult decision-makers appeared to be working from their own heteronormative values. These adults did not recognise that individual children may already have queer identities, denied to them within heteronormative family contexts; that individual children's own home backgrounds may not conform to dominant heteronormativity; or indeed that individual children may be well-able to negotiate the experience of difference on their own terms (Spence et al 2018).…”
Section: Adults and Children's Best Interestsmentioning
confidence: 99%